1999
DOI: 10.1038/45552
|View full text |Cite
|
Sign up to set email alerts
|

Atomic scale movement of the voltage-sensing region in a potassium channel measured via spectroscopy

Abstract: Voltage-gated ion channels are transmembrane proteins that are essential for nerve impulses and regulate ion flow across cell membranes in response to changes in membrane potential. They are made up of four homologous domains or subunits, each of which contains six transmembrane segments. Studies of potassium channels have shown that the second (S2) and fourth (S4) segments contain several charged residues, which sense changes in voltage and form part of the voltage sensor. Although these regions clearly under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
385
8
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(408 citation statements)
references
References 25 publications
14
385
8
1
Order By: Relevance
“…This confirms earlier suggestions of the location of S4 relative to the pore (Gandhi et al 2000; Elinder et al 2001). The large motion of R362 suggested by our results is compatible with both a helical screw motion (Catterall 1986; Guy and Seetharamulu 1986; Glauner et al 1999; Keynes and Elinder 1999; Gandhi et al 2000) and a pure twisting motion (Papazian and Bezanilla 1997; Cha et al 1999; Glauner et al 1999) of S4. Our estimated location and motion is also compatible with the results of other studies (Li-Smerin et al 2000; Loots and Isacoff 2000).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This confirms earlier suggestions of the location of S4 relative to the pore (Gandhi et al 2000; Elinder et al 2001). The large motion of R362 suggested by our results is compatible with both a helical screw motion (Catterall 1986; Guy and Seetharamulu 1986; Glauner et al 1999; Keynes and Elinder 1999; Gandhi et al 2000) and a pure twisting motion (Papazian and Bezanilla 1997; Cha et al 1999; Glauner et al 1999) of S4. Our estimated location and motion is also compatible with the results of other studies (Li-Smerin et al 2000; Loots and Isacoff 2000).…”
Section: Discussionsupporting
confidence: 85%
“…Cysteine accessibility studies suggest that the positive charges of S4 are either buried in the membrane or in the cytosol when the membrane is held at a hyperpolarized potential, and, in response to a depolarizing voltage pulse, the S4 charges move outward and exposes its three most external charges into the extracellular solution (Larsson et al 1996; Yang et al 1996; Yusaf et al 1996; Baker et al 1998; for review see Keynes and Elinder 1999). S4 is suggested to undergo a large-scale movement during activation of the channels, either a 180° rotation (Papazian and Bezanilla 1997; Cha et al 1999; Glauner et al 1999) or a helical screw motion with both a 180° rotation and a translational motion of 13.5 Å (Catterall 1986; Guy and Seetharamulu 1986; Glauner et al 1999; Keynes and Elinder 1999; Gandhi et al 2000). In a recent study on the Shaker K channel, we suggested that S4, in the activated state, was located just outside S5 with the most external positive charge of S4 (R362) closest to the pore (Elinder et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Circular dichroism spectra (CD) and CD melting experiments were measured on a JASCO J-810 spectropolarimeter equipped with a temperature-controlled water-bath. 1 H NMR spectra were carried out on a Bruker Avance 600 MHz NMR Spectrometer in D 2 O at 20°C.…”
Section: Bioassaymentioning
confidence: 99%
“…Due to a unique 4f n electronic configuration, lanthanide materials have been widely used as probes in luminescent resonance energy transfer (LRET) for bioassays and as reagents for diagnosis in magnetic resonance imaging (MRI) [1][2][3][4][5]. As chemical nucleases, lanthanide complexes have also shown a high efficiency to hydrolyze DNA and RNA without redox chemistry [6,7] There is great interest in the design and synthesis of small molecules which selectively target specific genes to inhibit biological functions in which particular DNA structures participate [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…49,50 Later measurements using spectroscopic techniques, particularly the LRET and another variation of FRET involving transfer between dyes and hydrophobic quenchers, suggested that the magnitude of movement was at most a couple of Angstroms (A ). 51,52 In contrast, a proposal based on the KvAP structure and state-dependent avidin/biotin accessibility experiments, 53 suggested that the S3-S4, therein named the paddle, might traverse most of the membrane thickness in a rigid body motion. Although there is not a consensus, most models of voltage-dependent gating seem to suggest that the S4 segment translates several angstroms and undergoes a~120 degree counter clockwise rotation.…”
Section: Molecular Mechanism Of Voltage Sensingmentioning
confidence: 99%